Konkurencyjność podstawowym celem Unii Europejskiej w zglobalizowanej gospodarce - Jankiewicz, Sławomir (Competition as the Main Objective of the European Union in the Globalised Economy, 2006)
Presently, we wonder which direction the EU will take. In the first place, we need to analyse what activities have been undertaken so far to make the member states competitive. In today's globalised world, competition is the key to fast and permanent improvement of living conditions in individual economies. Therefore, this article provides a concise outline of how competitive economies in selected member states are in the context of activities pursued to ensure their growth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 127-136